The New Yorker book of doctor cartoons and psychiatrist. (New York A.A. Knopf : Distributed by Random House, Inc., 1994)
101 cartoons.
Includes index.
Keywords: Physicians -- Caricatures and cartoons; Psychiatrists -- Caricatures and cartoons; American wit and humor, Pictorial; New Yorker (New York, N.Y. : 1925)